Legal Protection for Debtors over Separatist Creditors' Rights Related To Bankruptcy - Sutrisno Sutrisno (Jurnal Akta, 2020)
Indonesia, as a rechtstaat country, has consequences for the protection and respect of human rights of every class of society; for this reason the law in Indonesia must be able to realize the mandate of Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia. This includes legal protection for debtors over the rights of separatist creditor billing when bankruptcy occurs. In fact, the implementation of legal protection for debtors has not been able to do fairly up to now; this can occur because 1) the requirements for requesting bankrupt statements make it easy for debtors to go bankrupt, even though the debtor is actually in a state of solvency; 2) the PKPU mechanism has not provided extensive opportunities for debtors to improve company performance; and 3) efforts in bankruptcy are dominated by the authority of creditors. While, the problems that have resulted in the implementation of legal protection for debtors over the separatist creditor's collection rights so far are as follow: 1) there has been no funds for the costs of arranging and clearing bankrupt assets; 2) the bankrupt debtor is not cooperative and 3) the debtor sells / transfers his assets before being declared bankrupt. The method used in this paper is sociological juridical with non-doctrinal approach.Keywords: Debtor; Separatist Creditor Rights; Bankruptcy; Legal Protection.